“ET Plus”: Instability of the Diagnosis During Prospective Longitudinal Follow-up of Essential Tremor Cases - Iglesias-Hernandez, Daniella; Delgado, Nikki; McGurn, Margaret; Huey, Edward D.; Cosentino, Stephanie; Louis, Elan D. (Frontiers in Neurology, 2021)
Background: A recent consensus statement introduced the term “ET plus”. Although investigators have quantified the prevalence of ET plus in cross-sectional studies, patients with ET plus have not been tracked longitudinally; hence, there is no understanding of its stability over time. Methods: We present prospective, longitudinal phenotypic data on an ET cohort that was followed regularly at 18-month intervals (T1, T2, T3, T4) for up to 64 months. We assigned an ET or ET plus diagnosis to each case at each time interval. Results: There were 201 participants at baseline. The proportion with ET plus increased from 58.7% at baseline to 72.1% at T4 (p = 0.046). Of 172 (85.6%) who received a diagnosis of ET plus at one or more time intervals, the diagnosis was unstable (e.g., with reversion) in 62 (36.0%). We also assessed the stability of the clinical features of ET plus. Rest tremor was the most unstable clinical feature of ET plus; it was present in 59 participants, among whom it reverted from present to absent in 23 (39.0%). By contrast, for “memory impairment” (i.e., either mild cognitive impairment or dementia), the proportion who reverted from present to absent was only 21.3%. Conclusion: These data support our two a priori hypotheses: (1) the prevalence of ET plus would increase progressively, as it likely represents a more advanced stage of ET, and (2) the ET plus diagnosis would not be stable over time, as cases would fluctuate with respect to their phenotypic features and their assigned diagnoses. These findings suggest that ET and ET plus may not be distinct diagnostic entities.